A Framework for ICT-Oriented Sustainable Development through Mapping from ICT Concerns onto Sustainability Indicators - Mohammad Azadnia; Shamsossadat Zahedi (International Journal of Information and Communication Technology Research, 2018)
Sustainable development establishes a framework in which environmental policies and development strategies interact each other, and in the process of economic development, the long-term environmental value and human society is taken into account. In addition, ICT is rapidly transforming all aspects of human life and there is less of a sense of our lives that have not been directly or indirectly affected by the ICT. Our studies of the previous frameworks on the effects of ICT on the goals of sustainable development show that most of them fall into two categories. There are a number of frameworks that have introduced general and high-level ICT impacts on sustainability development in the first category, and the second category refers to some specific technologies or specific SDGs. In this paper, we have proposed a framework that addresses all technologies and concerns related to ICT and all SDGs. The main objective of this framework is to show the impact and mapping between SDGs, ICT concepts and technologies, ICT concerns, and ICT development success factors that can be used directly to evaluate the growth and degradation of each of them. The ICT concerns classified into four categories and mapped by ICT technologies and concepts to sustainable development and its goals and ICT development and its concerns.